Regulating open banking : comparative analysis of the EU, the UK and Taiwan - Tsai, Chang-hsien (Law professor); Peng, Kuan-Jung (Abingdon, Oxon ; New York, NY : Routledge, 2023)
FinTech transformations have brought changes to the global financial markets and merit the attention of financial regulators across jurisdictions. This book is one of the first ones of its kind to look at open banking (OB).It examines regulatory approaches to OB by taking a broad view of comparative legal systems and through perspectives of transaction costs, public choice, and institutional design. The book looks at the legal implications by engaging in a two-tiered comparative analysis: comparing between compulsory and voluntary approaches to OB policies and comparing the legal systems between the West (i.e., the EU and the UK) and an Asian economy (i.e., Taiwan).
"Routledge focus"--Cover.
Keywords: Banks and banking -- Security measures -- Case studies; Confidential communications -- Banking -- Case studies; Financial services industry -- Security measures -- Case studies; BUSINESS & ECONOMICS / Banks & Banking; LAW / Banking